PERILAKU PETANI MUDA DALAM AGRIBISNIS HORTIKULTURA DI KABUPATEN BANDUNG BARAT - Rani Andriani Budi Kusumo; Gema Wibawa Mukti; Endah Djuwendah (Universitas Galuh Ciamis, 2020)
Horticultural commodities are considered to have promising business opportunities. This has attracted the interest of young people to try in agriculture, both in the on farm and off farm sectors. This study aimed to describe the behavior of young farmers in doing horticultural agribusiness in Bandung Barat Regency. This research was conducted with a quantitative approach. Respondents in this study were 120 people and were farmers under the age of 40 with randomly selected. Data were analyzed using descriptive statistics. The results showed in general the behavior of young farmers in running horticultural agribusiness was not different from the previous generation. But the prominent character of young farmers in running horticultural agribusiness is the ability of farmers to find information and be responsive to change by taking innovative steps. To run a business, farmers are required not only to be experts in the production process, but also to have managerial skills in a results-oriented business.